SURGICAL OUTCOME OF SUPRACONDYLAR AND INTERCONDYLAR FRACTURES FEMUR IN ADULTS TREATED WITH DYNAMIC CONDYLAR SCREW - Ali, Iftikhar; Din, Shahab ud (Journal of Postgraduate Medical Institute, 2011)
Objective: To evaluate the surgical outcome of supracondylar and intercondylar fractures of femur in Methodology: This descriptive study was carried out in department of Orthopedics, Lady Reading Hospital Peshawar from October 2006 to October 2007. Thirty-five consecutive adult patients with supracondylar and intercondylar femur fractures fulfilling the inclusion criteria were managed with dynamic condylar screw and were followed for a minimum of six months post-operatively. Relevant data like time to union, knee range of movement and complications associated with these fractures treated with dynamic condylar screw was recorded. Results: In 45.71% cases road traffic accident was responsible for the fracture followed by 28.57% cases due to fall from height, and 25.71% cases due to firearm injury. 74.28% fractures were closed fractures and 25.71% fractures were open. Average time of union was 15 weeks. Two patients (5.71%) had delayed union while two patients (5.71%) had non-union. There were six patients with knee stiffness and two with limb shortening of up to 1.5 cm. Infection was noted in two patients, treated successfully with debridement and I.V. antibiotics. Two patients developed wound hematoma. The overall outcome were good to excellent in 26 patients (74.28%). Moderate outocme were obtained in three patients (8.57%) and poor in six patients (17.14%). Conclusion: The dynamic condylar screw is an easy, less technically demanding and rewarding method of treatment for supracondylar and intercondylar fracture of femur in adults. adults treated with dynamic condylar screw.